Hubungan Panjang-Berat dan Faktor Kondisi Ikan Kembung Lelaki (Rastrelliger kanagurta) yang Didaratkan di Pelabuhan Perikanan Pantai Lempasing Bandar Lampung - Qadar Hasani; Irvan Hambali; Abdullah Aman Damai; Suparmono Suparmono; David Julian; Luluk Irawati (Jurnal Sumberdaya Akuatik Indopasifik, 2023)
The increase in the volume of catches and the price of mackerel in Bandar Lampung in recent years can encourage more intensive and exploitative fishing efforts. The aims of this study is analyze the length-weight relationship, condition factors, and growth patterns of Indian mackerel (Rastrelliger kanagurta) landed at the Lempasing Fishing Port, as basic information for the management of R. kanagurta resources in the waters of Lampung Bay and its surroundings. Samples of Indian mackerel were obtained from fishs landed at Lempasing Fishing Port during July-Sept 2022. The fish samples were measured for length and weight, then analyzed for length distribution, condition factors and length-weight relationships. The length of the fish landed at the Lempasing Fishing Port ranged from 170–282 mm. The smallest fish size in the class interval 170-184 mm. The size of the most caught fish are in the class interval of 230–240 mm. The highest condition factor value of 1.02 was found in the smallest fish class interval. Condition factor showed that the values were not significantly different from 1. The equation of length-weight relationship is W=0.0017L2.086 with a determination coefficient value (R²) of 0.811. The growth pattern is negative allometric. This illustrates that Indian mackerel landed at the Lempasing Fishing Port tended to be thin. Further research related to reproductive patterns, gonadal maturity index, composition of catch number, catch productivity periodicly and sustainable is urgently needed for precise and sustainable management of Indian mackerel resources.